Narrative Connectedness: A Chain for Understanding Others in The Philosophy of Eleonore Stump - Bernard Subang Hayong (Jurnal Filsafat "WISDOM", 2022)
This essay aims to explore Eleonore Stump’s insights on narrative as a means of knowing others and to defend narrative cognitivism. Central to this defense is an examination of the narrative analysis in mediating second-person experience as a tool to gain both self-understanding and understanding others. This study is a combination of the expository, the analytical, and the critical methods. It is expository because it aims to understand how Stump explores the variant variable in seeking the meaning and explanation of human interaction. It is analytical because it examines how second-person experience can be communicated in narrative. And it is critical because it introduces a methodological concept in dealing with her thoughts and demonstrates in which sense her approach is tenable or not. In developing this approach, I introduce the second-person perspective and the nature of knowledge that is acquired through narrative. I conclude with a discussion of the contribution of narrative connectedness to the understanding of the other as a person. This article will show that narrative connectedness is a significant form of reasoning, a medium for understanding, and an instrument for self-expression.